Vitamin D Deficiency and Associated Factors in Children: A Multicenter Study of 21,811 Samples in Southern China - Chuican Huang; Sijia Liu; Chen Cheng; Shiyun Chen; Qing Luo; Yan Huang; Yanxian Yao; Xixia Ye; Haizhen Wang; Liangyi Luo; Junwei Xie; Hongai Li; et al. (International Journal of Public Health)
ObjectiveTo investigate the prevalence of vitamin D deficiency (VDD) in children/adolescents in extreme southern China.MethodsThis multicenter, cross-sectional study included 21,811 children aged 0–18 years from 18 districts in Hainan Province, using a multistage stratified random sampling method from January 2021 to March 2022.ResultsSerum 25(OH)D levels decreased with age (p trend <0.001). VDD prevalence increased significantly from 3.7% (95% CI: 3.2, 4.3) in children aged 0–3 years to 43.5% (95% CI: 42.1, 45.0) in those aged 13–18 years. Girls and urban residents showed higher deficiency rates. Adolescents (13–18 years) had the highest prevalence of VDD (43.5%), while toddlers (0–3 years) had the lowest (3.7%). Factors influencing vitamin D status included gender, urban residency, and breastfeeding duration. Seasonal variations showed higher deficiency rates in autumn, particularly among preschoolers. Regional differences were noted, with the highest deficiency in semiarid and subhumid zones for various age groups.ConclusionA significant increase in VDD with age, particularly among adolescents, urban girls, and during autumn, emphasizing the need for targeted strategies.